TP53 R273C Mutation Is Associated With Poor Prognosis in LGG Patients - Zhang, Jian; Liu, Minglu; Fang, Yujie; Li, Jinlong; Chen, Yin; Jiao, Shunchang (Frontiers in Genetics, 2022)
Purpose: With the progress of immunotherapy in cancer, hotspot mutations of common oncogenes and tumor suppressors are becoming new potential therapeutic targets. TP53 R273C mutation is one of the hotspot mutations of TP53, and it has higher frequency in lower grade glioma (LGG). However, the function of this mutation and its prognostic significance in LGG are not yet clear. Methods: To address this question, RNA sequencing, clinical, and SNP data of LGG patients from the TCGA database were downloaded. The Kaplan-Meier (KM) method was used for survival analysis. Immune cell populations in this cohort were assessed via MCP counter and CIBERSORT. DNA damage repair scores were calculated by GSVA analysis. WGCNA was conducted to identify genes related to TMB. Results: In the context of IDH1/2 mutation, LGG patients with TP53 R273C mutation had a worse prognosis than other mutation types and wild-type. This conclusion was still valid in LGG patients who had received chemotherapy or radiotherapy. Taken into consideration of the 1p19q co-deletion status, it was found that patients with both R273C mutation and 1p19q non-codeletion had the worst prognosis. Further analysis showed that LGGs with TP53 R273C mutation had a higher M2 macrophage infiltration and tumor mutation burden (TMB) than TP53 wild type LGGs and higher TMB indicated poor prognosis in LGG patients. Furthermore, we identified genes which could be associated with higher M2 macrophages infiltration and TMB in LGGs with TP53 R273C mutation. Conclusion: The study indicates that TP53 R273C mutation is very likely oncogenic and may be used as an indicator of prognosis in LGG patients.